2018
DOI: 10.1155/2018/5185460
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Characteristics of Unsaturated Loess and the Safety Detection of the Road Subgrade Based on GPR

Abstract: We present a moisture content and permittivity model to simultaneously detect and estimate defects in loess subgrade. Based on the ground-penetrating radar (GPR) method, the dielectric properties of loess in the northwest of China and the imaging feature of the moisture content of different strata were studied. The relative permittivity of loess with different moisture contents was experimented in the laboratory. It was found that the relative permittivity of unsaturated loess was positively related to moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The data of key points of hyperbolic curves are fitted by conjugate gradient method, and the hyperbolic formulas are obtained. The values of long and short axis are obtained by comparing hyperbolic formulas with (5). The detailed data are listed in Table 1.…”
Section: Imaging Characteristic Analysis Of Objects With Differentmentioning
confidence: 99%
See 2 more Smart Citations
“…The data of key points of hyperbolic curves are fitted by conjugate gradient method, and the hyperbolic formulas are obtained. The values of long and short axis are obtained by comparing hyperbolic formulas with (5). The detailed data are listed in Table 1.…”
Section: Imaging Characteristic Analysis Of Objects With Differentmentioning
confidence: 99%
“…The conjugate gradient method is also used to realize hyperbolic formula fitting. And the values of long and short axis hyperbolic formula are obtained by comparing hyperbolic formulas with (5). The detailed data are listed in Table 2.…”
Section: Imaging Characteristic Analysis Of Objects With Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, domestic and foreign scholars have deeply studied on the dielectric properties of soil with fruitful results. They found that the dielectric properties were not only affected by water content, but also affected by soil type, composition, texture, bulk density, temperature, dry density, porosity, saturation, humidity and test frequency (Chen et al, 2012;Liao et al, 2016;Christian et al, 2017;Lv et al, 2018;Dong et al, 2020;Xiao et al, 2020;Pan et al, 2021). However, the existing studies have built different dielectric constant models for the different soil types.…”
Section: Introductionmentioning
confidence: 99%